Ethics in a Christian context. -- - Lehmann, Paul Louis, 1906-1994 (Harper & Row, 1963)
Part One describes just what the method of a Christian ethic as a theological discipline involves. Part Two extends the methodological description by contrasting theological ethics with the tradition of Western moral philosophy as represented by Aristotle, Kant, James, Weiss, Fromm and Brandt.